Schmidt's Syndrome - Amra Rehman; Sairam Ahmed (ziauddin University, 2024)
Introduction: Schmidt's syndrome is a rare disease which is a one of the types of autoimmune polyglandular autoimmune syndrome. In these polyglandular autoimmune syndrome autoimmunity with auto-antibodies directed against different endocrine organs suggest in the pathogenesis of the disease. In addition there is role of genetic and familial predisposition of the disease. Autoimmune thyroid disease in combination with Addison disease is the most common presentation. In addition Diabetes mellitus Hyperparathyroidism, Pernicious Anemia, Hypogonadism, Vitiligo, Chronic atrophic gastritis, Chronic autoimmune hepatitis, Alopecia, Myasthenia gravis, Rheumatoid arthritis, Sjögren's syndrome and Thrombocytic purpura may or may not be present. So in patients suffering from one endocrine hormone deficiency should be thoroughly looked for the deficiency of other hormones. We present a case of 23 year old man who present with symptoms of gastritis and was refractory to treatment and on further evaluation was diagnosed as a case of Schmidt syndrome. Key Words: Schmidt's Syndrome, Autoimmune Hypothyroid, Polyglandular.